2009
DOI: 10.1021/jm901057p
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro-pegylated Chalcones as Positron Emission Tomography Probes for in Vivo Imaging of β-Amyloid Plaques in Alzheimer’s Disease

Abstract: This paper describes the synthesis and biological evaluation of fluoro-pegylated (FPEG) chalcones for the imaging of beta-amyloid (Abeta) plaques in patients with Alzheimer's disease (AD). FPEG chalcone derivatives were prepared by the aldol condensation reaction. In binding experiments conducted in vitro using Abeta(1-42) aggregates, the FPEG chalcone derivatives having a dimethylamino group showed higher Ki values (20-50 nM) than those having a monomethylamino or a primary amine group. When the biodistributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 35 publications
(107 reference statements)
5
49
0
1
Order By: Relevance
“…In vitro binding experiments to evaluate the binding affinity of the chalcones for Aβ were performed in suspensions of Aβ (1-42) aggregates with [ 125 I]4-dimethylamino-4'-iodochalcone (DMIC) which is a high-affinity Aβ ligand with a chalcone backbone as described in our previous papers [17][18][19][20] . The inhibition constant (Ki) values of 2-4 indicated that the binding affinity of these compounds to Aβ aggregates was affected by the length of the ethyleneoxy group in the chalcone backbone.…”
Section: In Vitro Binding Assays Using Aβ1-42 Aggregatesmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro binding experiments to evaluate the binding affinity of the chalcones for Aβ were performed in suspensions of Aβ (1-42) aggregates with [ 125 I]4-dimethylamino-4'-iodochalcone (DMIC) which is a high-affinity Aβ ligand with a chalcone backbone as described in our previous papers [17][18][19][20] . The inhibition constant (Ki) values of 2-4 indicated that the binding affinity of these compounds to Aβ aggregates was affected by the length of the ethyleneoxy group in the chalcone backbone.…”
Section: In Vitro Binding Assays Using Aβ1-42 Aggregatesmentioning
confidence: 99%
“…Indeed, it was reported that several Aβ probes with single-digit nanomolar Ki values for the Aβ aggregates successfully stained the Aβ plaques in brain sections of the Tg2576 mice by in vitro autoradiography 25,26 . In addition, it has been shown that chalcone derivatives with a dimethylamino group at the third position can be used to visualize Aβ plaques by in vitro autoradiography 19,27 . Thus, chalcone derivatives with a dimethylamino group in the 3-phenyl ring may be more suitable than those with an alkoxy group with respect to binding of the Aβ plaques in the brain.…”
Section: In Vitro Autoradiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have reported that flavonoids including chalcone, flavone, and aurone serve as useful molecular scaffolds in the development of imaging agents for β-amyloid plaques in the brain [23][24][25][26][27][28] . Initially, we designed and synthesized four 99m Tc-labeled In the present study, to develop more useful 99m Tc imaging agents for the clinical diagnosis of AD, we synthesized two flavone and aurone derivatives with BAT as a chelation ligand.…”
Section: Ono Et Al 3/38mentioning
confidence: 99%
“…Based on this success, efforts were made to search for comparable 99m Tc imaging agents that target binding sites on -amyloid plaques in the brain of AD patients. Several 99m Tc-labeled imaging probes have been developed (Figure 1), but no clinical study of them has been reported [19][20][21][22] .Recently, we have reported that flavonoids including chalcone, flavone, and aurone serve as useful molecular scaffolds in the development of imaging agents for β-amyloid plaques in the brain [23][24][25][26][27][28] . Initially, we designed and synthesized four 99m Tc-labeled In the present study, to develop more useful 99m Tc imaging agents for the clinical diagnosis of AD, we synthesized two flavone and aurone derivatives with BAT as a chelation ligand.…”
mentioning
confidence: 99%